2020
DOI: 10.1109/access.2020.3039410
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Traffic Flow Prediction Using the Modified Elman Recurrent Neural Network Optimized Through a Genetic Algorithm

Abstract: Traffic stream determining is an essential part of the intelligent transportation management system. Precise prediction of traffic flow provides a basis for other tasks, like forecasting travel time. While traditional methods have some merits for improving traffic prediction precision in some ways, high precision, considering different circumstances, is still difficult to achieve. This paper presents a short-term traffic flow prediction model based on the Modified Elman Recurrent Neural Network model (GA-MENN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 72 publications
0
20
0
1
Order By: Relevance
“…Sadeghi-Niaraki et al presented a short-term traffic flow prediction model [14] based on the modified Elman recurrent neural network (ERNM) model to improve traffic prediction model precision. They used a modified ERNM method optimized through a genetic method, and they considered weather conditions, weekday, hour and day's classification to forecast the vehicle velocity in Tehran streets and highways, but they did not forecast traffic fluxes.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Sadeghi-Niaraki et al presented a short-term traffic flow prediction model [14] based on the modified Elman recurrent neural network (ERNM) model to improve traffic prediction model precision. They used a modified ERNM method optimized through a genetic method, and they considered weather conditions, weekday, hour and day's classification to forecast the vehicle velocity in Tehran streets and highways, but they did not forecast traffic fluxes.…”
Section: Related Workmentioning
confidence: 99%
“…Table 2 summarizes the information about the related work documented in terms of the dataset used, the processing techniques that were used and the learning process objective. This analysis allows to perceive different forecasting objective [13,15,21,22], works that did not sufficiently detail the dataset used or the conditions of use [17,19] or were developed for very different road models [14,18], so our option was to test several deep learning methods in order to evaluate them in terms of accuracy and efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…Instead of the error backpropagation, we can use metaheuristic approaches to train a model. There exists a range of interesting studies including [40] where the authors used Genetic Algorithm or [15] where Ant Colony Optimisation was employed. Interesting research was delivered by Abdulkarim and Engelbrecht [1] who concluded their study on the application of dynamic Particle Swarm Optimisation to neural network training by stating, that for the time series they tested, dynamic Particle Swarm Optimisation ensured forecasting error to be the same for a standard neural architecture and a recurrent one.…”
Section: Related Work On Time Series Forecastingmentioning
confidence: 99%
“…The increasing in complexity of real-world applications has motivated the development of computational intelligence techniques based on artificial neural networks [1] , fuzzy logic [2] , evolutionary computation [3] , [4] , and others, as useful tools for solution of practical problems [5] , [6] , [7] , [8] , [9] . Recently, the combination of different intelligent systems with traditional computational approaches has been proposed in different fields of research in order to develop more efficient tools [10] , [11] , [12] , [13] . In the context of computational modeling of experimental data, type-2 fuzzy systems have attracted considerable attention by researches due to its interpretable rule-based structure with capability to treat nonlinearity and uncertainty [14] , [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%